The Importance of Visual Learning Media Innovation in Facilitating the Ability to Recognize Letters of the Alphabet for Children Aged 4-5 Years - Salsabila Amalia; Heri Yusuf Muslihin; Taopik Rahman (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
A person in early childhood is at a fundamental age, and children need to be properly stimulated in a number of areas of development. One aspect of development that needs to be stimulated is the aspect of language development and one of the language skills is reading. One of the basic aspects of reading skills that needs to be stimulated in early childhood is the ability to recognize letters of the alphabet as a basis for learning to read at an early stage. In this regard, research was carried out using descriptive qualitative methods at RA Assidiqiyyah and RA PUI Al-Fatwa. The research was intended to find out educators' understanding of the importance of visual learning media innovation in facilitating the ability to recognize letters of the alphabet, the ability of children aged 4-5 years to recognize letters of the alphabet, and the use of learning media to facilitate the ability to recognize letters of the alphabet for children aged 4-5 years. From the research that has been done, it is found that the media used is still not innovative, even though educators understand the importance of visual media innovation very well.